Tourism, Foreign Direct Investment, and Energy Consumption: Evidence from Causality Analysis in ASEAN - Putri Dea Nabilah; Deni Kusumawardani (Jurnal Riset Ilmu Ekonomi, 2026)
ASEAN’s rapid economic expansion has been increasingly supported by tourism growth and foreign direct investment (FDI), both of which contribute significantly to regional development while simultaneously intensifying energy demand. This study examines the dynamic relationships among tourism, FDI, and energy consumption in ASEAN using a panel Vector Error Correction Model (VECM) and Wald causality tests. The results confirm the existence of both short-run and long-run interdependencies among the variables. In the short run, tourism significantly stimulates FDI inflows by expanding market opportunities and demand for tourism-related industries. Conversely, energy consumption negatively affects tourism, indicating that environmental pressure and intensive energy use may reduce tourism competitiveness. In the long run, the strongest relationship occurs between FDI and energy consumption, suggesting that ASEAN’s economic growth remains highly dependent on energy-intensive industrialization and infrastructure development. The findings imply that although ASEAN economies are gradually diversifying through tourism-led service expansion, regional growth continues to rely heavily on industrial and energy-driven activities. Therefore, ASEAN countries need integrated policies that combine tourism development, investment expansion, and sustainable energy management to support long-term economic competitiveness and environmental sustainability.